2015
DOI: 10.5152/tjar.2014.03521
|View full text |Cite
|
Sign up to set email alerts
|

Anaesthetic Method Preference of Obstetricians for Caesarean Section

Abstract: Original Article / Özgün Araştırma Amaç: Anestezistler sezaryen için önceki yıllara göre daha yük-sek oranda rejyonal anestezi uygulamaktadır. Yaptığımız çalışma-da obstetrisyenlerin bu değişime yaklaşımlarını değerlendirmeyi amaçladık.Yöntemler: İnternet aracılığıyla obstetrisyenlerin elektronik posta adreslerine anket formları gönderildi. Anket formlarını 195 obstetrisyen cevapladı. Bu ankette obstetrisyenlerin cinsiyet, yaş, ça-lıştıkları bölge, çalıştıkları kurum, uzman olarak çalıştıkları süre, sezaryen a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 5 publications
0
2
1
Order By: Relevance
“…In other words, it can be said that RA is not chosen because of its advantages but rather as an alternative to general anaesthesia in cases where the risk of general anaesthesia is high. Dağlı et al investigated the preferences of obstetricians regarding regional anaesthesia during Caesarean section operations 12. In contrast to our findings, they reported that 80% of obstetricians preferred regional anaesthesia for these operations.…”
Section: Discussioncontrasting
confidence: 98%
“…In other words, it can be said that RA is not chosen because of its advantages but rather as an alternative to general anaesthesia in cases where the risk of general anaesthesia is high. Dağlı et al investigated the preferences of obstetricians regarding regional anaesthesia during Caesarean section operations 12. In contrast to our findings, they reported that 80% of obstetricians preferred regional anaesthesia for these operations.…”
Section: Discussioncontrasting
confidence: 98%
“…Advantages of SA over GA are that its effect begins quicker; the hospitalization length, nausea/vomiting at the end of the operation, mortality, morbidity and need for postoperative analgesic are lower; patient satisfaction is greater, and it provides more localized and intense blockage than epidural anesthesia [ 17 , 18 ]. In some patients and operations, SA may be a more appropriate option; for example, SA is usually preferred for pregnant women because the transfer of the administered medication to the fetus is minimized.…”
Section: Discussionmentioning
confidence: 99%
“…Regional anesthesia is the preferred modality for Cesarean deliveries as it avoids the maternal risks of general anesthesia, such as aspiration of gastric contents and difficulty with airway management. Furthermore, it allows administration of fewer drugs, resulting in a better adverse effect profile and a lower risk of anaphylaxis; ensures an awake mother and an attentive neonate, thereby facilitating early breastfeeding and maternal bonding; allows early mobilization and imparts better postoperative analgesia 2,3 . Spinal anesthesia is the most frequently used regional anesthesia technique for Cesarean deliveries because of its relative ease of administration and better safety profile.…”
Section: Introductionmentioning
confidence: 99%